(untitled) (Eurasian Journal of Ecology, 2021)
Investigation of the adsorption of copper and zinc ions by sorbents based on plant waste – cake and husk of sunflower seeds. Nowadays water bodies contain a huge amount of pollutants that are products of human activity. Heavy metals exceeding the maximum permissible concentrations (MPC) are among the most common pollutants in wastewater. The most popular and effective ways to reduce the concentration of heavy metal ions in wastewater are sorption methods of purification. Therefore, there is an urge to create new adsorbents that have a lower price than existing on the market, as well as are effective and environmen- tally friendly. The aim of this work is to study the adsorption activity of waste based on husk (SH) and cake (SC) of sunflower seeds in relation to copper and zinc ions. The maximum degree of extraction using SH reaches (88 ± 3.43) % for Cu 2+ and (81.4 ± 5.53) % for Zn 2+ . Grinding the SH leads to an increase in the extraction degree up to (93 ± 2.57) % for Cu 2+ and to (89 ± 2.35) % for Zn 2+ . In the case of SC, the maximum extraction degree reaches (72 ± 4.98) % for Cu 2+ and (80 ± 3.07) % for Zn 2+ . Sorbents were modified in order to increase the extraction degree. The degree of extraction of Cu 2+ and Zn 2+ ions by SH carbonated coal reaches (95±2,29)% for Сu 2+ and (96±3,41)% for Zn 2+ . In the case of SC carbonated coal, the extraction degree reaches (93±2,98)% and (35±4,24)% for Cu 2+ and Zn 2+ respectively. The extraction degree of Cu 2+ and Zn 2+ ions by acid-treated SH and SC carbonated coals reaches 100%. As a result of studying the kinetics of the processes under study, it was found that the in- teraction is described by a pseudo-second order model in the case of the adsorption of: 1) Cu 2+ and Zn 2+ on the SH; 2) Cu 2+ on the SC. For the adsorption of Zn 2+ on the SC the pseudo-first order fits better. In the case of modified sorbents, the process is described by a pseudo-second order model for the adsorp- tion of : 1) Сu 2+ and Zn 2+ by acid-treated SH carbonated coal; 2) Сu 2+ and Zn 2+ by SC carbonated coal; 3) Zn 2+ ions by acid-treated SC carbonated coal; 4) Сu 2+ ions by SH carbonated coal. The pseudo-first order model describes the adsorption of Zn 2+ ions by HS carbonated coal and Сu 2+ ions by acid-treated CS carbonated coal. Key words: sunflower husk, sunflower cake, adsorption, copper ions, zinc ions, kinetics.